Sticky situation: best practice to secure endotracheal tubes in the operating room - Davies, Adam; Murphy, Meagan; Monaghan, W. Patrick Monaghan; Cushenbery, Cameron (International Journal of Advanced Nursing Studies, 2014)
Background: Tape is the standard means of securing endotracheal tubes in the surgical environment to prevent accidental extubation. This study utilizes a mannequin model to examine the amount of force required to dislodge endotracheal tubes secured with four different varieties of commercially available tape and three different taping methods. This study also incorporates different angles of applied force and varying mannequin positions to simulate conditions often encountered in the operating room. Methods: An airway trainer mannequin was intubated using a standard cuffed endotracheal tube and secured with one of four varieties of tape and one of three taping methods in randomly assigned order. The mannequin was placed in either the supine, lateral, or prone position. The endotracheal tube was then attached to a digital force meter and constant manual force applied in one of three planes (laterally to right, vertically, or laterally to left) until the cuff was removed from the trachea. Force measurements were recorded and analyzed. Results: Securing the endotracheal tube to both the maxillary and mandibular borders with Durapore™ silk tape held the endotracheal tube in the strongest, requiring the greatest force to dislodge it from the airway. Angle of force also showed statistical significance. Conclusions: The amount of force required to dislodge endotracheal tubes is affected by tape type, taping method, and direction of force. Durapore™ silk tape applied to both maxillary and mandibular borders was superior at holding the endotracheal tube in place when compared to other tape varieties and taping methods. Keywords: Airway control, airway extubation, airway management, intubation, endotracheal intubation.